THE EFFECT OF OWNERSHIP STRUCTURE ON CORPORATE FINANCIAL PERFORMANCE: AN EMPIRICAL STUDY OF INDUSTRIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2020–2024 PERIOD - Salsa Vonni Indrayani; Ratih Kusumastuti; Mukhzarudfa; Wiwik Tiswiyanti (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study aims to analyze the effect of institutional ownership and managerial ownership on firm financial performance, measured using Tobin’s Q, in industrial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study adopts a quantitative approach using panel data regression with 70 observations from 14 companies selected through purposive sampling. The selection of the most appropriate model was conducted using the Chow test and the Hausman test, which indicate that the Fixed Effect Model (FEM) is the most suitable model for the analysis. The results show that, partially, both institutional ownership and managerial ownership do not have a statistically significant effect on Tobin’s Q. However, simultaneously, both variables have a significant effect on firm financial performance. These findings suggest that ownership structure mechanisms are more effective in explaining firm performance when operating simultaneously within a corporate governance framework. Based on agency theory, these results confirm that the combination of ownership mechanisms can serve as a more effective monitoring tool in reducing conflicts of interest between managers and shareholders. This study provides empirical contributions to the corporate governance literature in developing countries, particularly in the Indonesian industrial sector.